Novel use of a flowable collagen-glycosaminoglycan matrix (Integra™ Flowable Wound Matrix) combined with percutaneous cannula scar tissue release in treatment of post-burn malfunction of the hand—: A preliminary 6 month follow-up - Hirche, Christoph; Senghaas, Annika; Fischer, Sebastian; Hollenbeck, S. T.; Kremer, Thomas; Kneser, Ulrich (Burns, 2016)
Introduction - Long-term function following severe burns to the hand may be poor secondary to scar adhesions to the underlying tendons, webspaces, and joints. In this pilot study, we report the feasibility of applying a pasty dermal matrix combined with percutaneous cannula teno- and adhesiolysis. - Patients and methods - In this 6 month follow-up pilot study, we included eight hands in five patients with hand burns undergoing minimal-invasive, percutaneous cannula adhesiolysis and injection of INTEGRA™ Flowable Wound Matrix for a pilot study of this new concept. The flowable collagen-glycosaminoglycan wound matrix (FCGWM) was applied with a buttoned 2mm cannula to induce formation of a neo-gliding plane. Post treatment follow-up was performed to assess active range of motion (AROM), grip strength, Disabilities of the Arm, Shoulder and Hand (DASH) score, Vancouver Scar Scale (VSS) and quality of life Short-Form (SF)-36 questionnaire. - Results - No complications were detected associated with the treatment of FCGWM injection. The mean improvement (AROM) at 6 months was 30.6° for digits 2-5. The improvement in the DASH score was a mean of 9 points out of 100. The VSS improved by a mean of 2 points out of 14. - Discussion - The study demonstrates the feasibility and safety of percutaneous FCGWM for dermal augmentation after burn. Results from this pilot study show improvements in AROM for digits 2-5, functional scores from the patient's perspective (DASH) and scar quality (VSS). The flowable form of established INTEGRA™ wound matrix offers the advantage of minimal-invasive injection after scar release in the post-burned hand with a reduction in the risk of postsurgical re-scarring.